Synthesis of Tilapia Feed From a Mixture of Tarum Leaves (Indigosfera sp) and Fermented Shrimp Waste by EM-4 Probiotics - Bimantara Hidayah; Yuki Amru Alwansyah; Nove Kartika Erliyanti; Caecilia Pujiastuti (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
Feed is the most important thing in doing a tilapia fish farming. In a feed required appropriate and balanced nutritional content so that fish growth becomes faster. Shrimp waste and tarum leaves are an alternative raw material for the manufacture of tilapia feed because they have a fairly high protein content. The purpose of this study was to examine the comparative effect of adding the percentage of tarum leaf meal and EM-4 fermented shrimp waste on water content, ash content, protein content, fat content, and crude fiber content of feed. The research method used is using the EM-4 fermentation process on shrimp waste. The variations carried out were the concentration of the addition of EM-4 (14,16,18,20, and 22 ml) and the percentage of addition of Wet Shrimp Waste (WSW) and Tarum Leaf Powder (TLP) (90%WSW + 10%TLP, 80%WSW + 20%TLP, 70%WSW + 30%TLP, 60%WSP + 40%TLP, and 50%WSW + 50%TLP). The results showed that the addition of fermented WSW EM-4 and TLP had a significant effect on the protein, fat and crude fiber content, while the water and ash content did not have a significant effect. The best tilapia feed formulation results were obtained at a ratio of 60% WSW and 40% TLP using 18 ml of EM-4 with the results obtained for water, ash, protein, fat and crude fiber content each of 7.09%. ; 12.59%; 29.98%; 7.45%; and 3.49%.